Polyhydroxylated pyrrolidine and piperidine alkaloids from Adenophora triphylla var. japonica (Campanulaceae). - Asano, N; Nishida, M; Miyauchi, M; Ikeda, K; Yamamoto, M; Kizu, H; Kameda, Y; Watson, A; Nash, R; Fleet, G (2000)
Adenophora triphylla var. japonica (Campanulaceae) yielded two new alkaloids, the 6-C-butyl derivative of 2R,5R-bis(hydroxymethyl)-3R,4R-dihydroxypyrrolidine (DMDP) and alpha-1-C-ethyl-fagomine, together with the known alkaloids 1,4-dideoxy-1,4-imino-D-arabinitol, 1-deoxynojirimycin, and 1-deoxymannojirimycin. 6-C-Butyl-DMDP showed inhibitory activity toward almond beta-glucosidase (IC50 = 68 microM), whereas alpha-1-C-ethyl-fagomine inhibited bovine liver beta-galactosidase (IC50 = 29 microM).